Acdk1 gradient guides surface contraction waves in oocytes - Bischof, Johanna; Brand, Christoph A.; Schwarz, Ulrich S. (Nature Communications, 2017)
Surface contraction waves (SCWs) are prominent shape changes coupled to cell cycle transitions in oocytes. Here the authors show that SCWs are patterned by the spatiotemporal integration of two conserved modules, cdk1-cyclinB for cell cycle regulation and RhoA/Rok/NMYII for actomyosin contractility.